2020
DOI: 10.1029/2019jb018623
|View full text |Cite
|
Sign up to set email alerts
|

Cementation Failure Behavior of Consolidated Gas Hydrate‐Bearing Sand

Abstract: The macromechanical properties (strength, stiffness, stress-strain relationship, etc) of the hydrate-bearing sediment are often correlated with the hydrate cementation failure behavior. In this study, a consolidated drained triaxial shear test with X-ray computed tomography was conducted on a hydrate-bearing sediment with a hydrate saturation of 32.1% under 3 MPa effective confining pressure for revealing the cementation failure behavior. The hydrate occurrences were clearly identified to be cementing, grain-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 84 publications
4
69
1
Order By: Relevance
“…In all experiments, the specimens get bulged under axial loading, additional example in Seol et al (), rather than developing a dominant shear plane, as observed in some previous experiments (Higo et al, ; Wu et al, ; Yoneda et al, ). Development of a dominant shear plane is accompanied with lateral movements of the loading piston and high degree of discontinuity at specimen surface where it intersects the shear plane.…”
Section: Resultsmentioning
confidence: 68%
“…In all experiments, the specimens get bulged under axial loading, additional example in Seol et al (), rather than developing a dominant shear plane, as observed in some previous experiments (Higo et al, ; Wu et al, ; Yoneda et al, ). Development of a dominant shear plane is accompanied with lateral movements of the loading piston and high degree of discontinuity at specimen surface where it intersects the shear plane.…”
Section: Resultsmentioning
confidence: 68%
“…However, it has to be admitted that the partial volume effect would affect the thresholding segmentation to some extent (Soret & Bacharach, 2007). In the CT study relating to hydrate, this issue is usually solved by substituting some of the substances to anthor with a large difference in grayscale (like substituting NGH with XeH in this study) to make the grayscale range larger for reducing this impact (Chaouachi et al, 2015; Wu et al, 2020; Yang et al, 2016). In this paper, the pores are thought to be determined by Xe without Xe hydrate, during the pore parameter analysis and absolute permeability calculation.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Xenon gas (Xe) was used to generate xenon hydrates (XeH) due to its high X-ray 10.1029/2019JB019103 Journal of Geophysical Research: Solid Earth attenuation coefficient in comparison to NGH for enhanced phase contrast in obtained CT images. Meanwhile, the physical characteristics (such as structure type, stoichiometry, and adiabatic bulk modulus) are quite similar between XeH and NGH (Chaouachi et al, 2015;Ning et al, 2012;Wu et al, 2020). Additionally, XeH requires a much lower equilibrium pressure compared to NGH and thus makes the CT experiment which is conducted in a limited space safer (Chaouachi et al, 2015).…”
Section: Experimental Procedures and Test Conditionsmentioning
confidence: 99%
“…First, the REV was segmented into the sand phase and pore space phase according to the gray value, and the segmentation threshold was determined by repeatedly comparing the calculated and the real volumes. The specific method can be found in our previous study (Wu, Li, Liu, Sun, et al, 2020). The porosity of the REV was 36.4%, which was similar to that of the field investigation (Yoneda et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…When the consolidation was completed, a CT scan was conducted with a voxel size of 44 μm. More details about the specimen preparation process can be found in our previous study (Wu, Li, Liu, Sun, et al, 2020).…”
Section: 1029/2020jb020570mentioning
confidence: 99%